1972
DOI: 10.3758/bf03335463
|View full text |Cite
|
Sign up to set email alerts
|

Reversal learning in forebrain ablated and olfactory tract sectioned teleost, Carassius auratus

Abstract: Groups of goldfish with forebrain ablation and the olfactory tract sectioned were taught a food-motivated nondiscriminative choice in a Y-maze. Criterion choice behavior was followed by successive reversal learning. Both groups successfully acquired each task but the fish with forebrain ablation were slower to eliminate errors in the reversals than were the fish with the olfactory tract sectioned. There were no latency differences between groups on any tasks. It was concluded that the teleost forebrain may, in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
9
0

Year Published

1972
1972
2020
2020

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(11 citation statements)
references
References 10 publications
2
9
0
Order By: Relevance
“…Although the majority of experiments reviewed above, in which tract section alone was performed, showed no difference between these and unoperated animals, the study of Frank et al (1972) did detect a difference. Further, Cain (1974) examined the results of damage to the mammalian olfactory bulb and concluded that the effects are far more extensive than a mere loss of smell.…”
Section: Fish Telencephalon and Learningmentioning
confidence: 76%
“…Although the majority of experiments reviewed above, in which tract section alone was performed, showed no difference between these and unoperated animals, the study of Frank et al (1972) did detect a difference. Further, Cain (1974) examined the results of damage to the mammalian olfactory bulb and concluded that the effects are far more extensive than a mere loss of smell.…”
Section: Fish Telencephalon and Learningmentioning
confidence: 76%
“…In accordance with the existence of trade-offs between cognitive abilities, as proposed by Tellos-Ramos and colleagues (2019) , the ecology of the guppy might favour spatial memory rather than the advanced learning abilities investigated here. Second, cognitive processes involved in the ability to adopt an efficient learning strategy are controlled by a specific region in the telencephalon ( Frank et al, 1972 ; Izquierdo et al, 2016 ; López et al, 2000 ; Watanabe, 2012 ). Primates have among the largest relative telencephalon sizes in the animal kingdom ( Finlay and Darlington, 1995 ), and telencephalon neuron number and density in parrots and many songbirds are equivalent to those of primates ( Olkowitcz et al, 2016 ).…”
Section: Discussionmentioning
confidence: 99%
“…In this case A+ B− becomes A− B+. The switch in reward contingency is thought to be more cognitively demanding and involves different cognitive processes and brain regions from those for the initial discrimination task ( Frank et al, 1972 ; Izquierdo et al, 2016 ; López et al, 2000 ; Watanabe, 2012 ; Buechel et al, 2018 ). The initial discrimination tests for associative learning ability, while the ability to reverse and learn the new reward contingency tests behavioural flexibility ( Bitterman, 1965 ; Bond et al, 2007 ; Izquierdo et al, 2016 ; Shettleworth, 2010 ).…”
Section: Introductionmentioning
confidence: 99%
“…Following Overmier and Hollis' (1990) review of Frank, Flood, and Overmier (1972) and Warren's (1961) experiments, the general conclusion is that telencephalic ablated fish performed poorly in a spatial, successive reversal task compared to both normal fish or subjects with their olfactory bulbs removed. These early findings confirm the role of the telencephalon in spatial behavior of fish, but they also relate to the general debate about the existence of successive reversal learning in fish.…”
Section: Spatial Learningmentioning
confidence: 99%